Patient navigator team perceptions on the implementation of a citywide breast cancer patient navigation protocol: a qualitative study - Stephanie Loo; Katelyn Mullikin; Charlotte Robbins; Victoria Xiao; Tracy A. Battaglia; Stephenie C. Lemon; Christine Gunn; the TRIP Consortium (BMC, 2022)
Abstract Background In 2018 Translating Research Into Practice (TRIP), an evidence-based patient navigation intervention aimed at addressing breast cancer care disparities, was implemented across six Boston hospitals. This study assesses patient navigator team member perspectives regarding implementation barriers and facilitators one year post-study implementation. Methods We conducted in-depth qualitative interviews at the six sites participating in the pragmatic TRIP trial from December 2019 to March 2021. Navigation team members involved with breast cancer care navigation processes at each site were interviewed at least 12 months after intervention implementation. Interview questions were designed to address domains of the Consolidated Framework for Implementation Research (CFIR), focusing on barriers and facilitators to implementing the intervention that included 1) rigorous 11-step guidelines for navigation, 2) a shared patient registry and 3) a social risk screening and referral program. Analysis was structured using deductive codes representing domains and constructs within CFIR. Results Seventeen interviews were conducted with patient navigators, their supervisors, and designated clinical champions. Participants identified the following benefits provided by the TRIP intervention: 1) increased networking and connections for navigators across clinical sites (Cosmopolitanism), 2) formalization of the patient navigation process (Goals and Purpose, Access to Knowledge and Information, and Relative Advantage), and 3) flexibility within the TRIP intervention that allowed for diversity in implementation and use of TRIP components across sites (Adaptability). Barriers included those related to documentation requirements (Complexity) and the structured patient follow up guidelines that did not always align with the timeline of existing site navigation processes (Relative Priority). Conclusions Our analysis provides data using real-world experience from an intervention trial in progress, identifying barriers and facilitators to implementing an evidence-based patient navigation intervention for breast cancer care. We identified core processes that facilitated the navigators' patient-focused tasks and role on the clinical team. Barriers encountered reflect limitations of navigator funding models and high caseload. Trial registration Clinical Trial Registration Number NCT03514433 , 5/2/2018.